Germination of Syzygium cumini (L.) Skeels. - DEDEN MUDIANA (Biodiversitas Journal of Biological Diversity, 2007)
Syzygium cumini belongs to Myrtaceae family. It is known as duwet, juwet, jamblang, etc in Indonesia. Although this species is well known by Indonesian, the information about character of growth this species still limited. Germinations process of this species is one of important information that must be known. This research aims to know about germinations of seed and growth of seedling this species. Seed germinations start at 18 day after sowing. The percentage of seed viability was 53.33%.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: germination, Syzygium cumini (L.) Skeels